Effects of Exercise and Hypoxia on Heart Rate Variability and Acute Mountain Sickness - Mairer, K.; Wille, M.; Grander, W.; Burtscher, M. (International Journal of Sports Medicine, 2013)
Acute mountain sickness (AMS) is a common condition among non-acclimatized individuals ascending to high altitude. Exercise, a characteristic feature of hiking and mountaineering, has been suggested to exacerbate AMS prevalence and to cause modifications of the autonomic nervous system. A reduction of the heart rate variability (HRV) is a common finding during acute hypoxia, however characteristics of HRV during exercise in subjects suffering from AMS are unknown. Therefore, the aim of the present study was to investigate the effects of acute normobaric hypoxia (FiO2=11.0% ≙ 5 500 m) at rest (PHE) and during exercise (AHE) on the cardiac autonomic function and the development of AMS in 20 healthy, male individuals. HRV recordings were performed during normoxia and after 2, 4, 6 and 8 h in hypoxia during PHE and AHE, respectively. AMS was assessed using the Lake Louise Score. During PHE 50% of participants developed AMS and 70% during AHE (p=0.22). The analysis of HRV data showed a significant reduction of total power (TP), high frequency (HF) and low frequency (LF) components and an increase of the LF:HF ratio during PHE, however without further modification during AHE. Exercise did not increase AMS prevalence or severity, but increased “non-gastrointestinal” symptoms including headache, fatigue and dizziness. HRV indices were not related to the overall incidence of AMS or the development of “non-gastrointestinal” symptoms but we detected significant correlations between gastrointestinal complaints and HRV components. Thus, we suggest that the cardiac autonomic modulation during acute normobaric hypoxia does not play an important role in the development of AMS, but seems to be related to gastrointestinal complaints at high altitude. However, the influence of moderate exercise on HRV and AMS is minor, only “non-GI” symptoms seem to be exacerbated when exercise is applied.
Keywords: autonomic nervous system; acute mountain sickness; normobaric hypoxia; high altitude; exercise